Comparison of Retrograde Balloon Dilatation and Laparoscopic Pyeloplasty for Treatment of Ureteropelvic Junction Obstruction: Results of a 2-Year Follow-Up - Xu, Ning; Chen, Shao-Hao; Xue, Xue-Yi; Zheng, Qing-Shui; Wei, Yong; Jiang, Tao; Li, Xiao-Dong; Huang, Jin-Bei; Cai, Hai (PloS one, 2016)
To evaluate the efficacy of laparoscopic pyeloplasty relative to retrograde balloon dilatation for the treatment of ureteropelvic junction obstruction (UPJO). This retrospective study enrolled UPJO patients with stricture length < 2 cm who had been treated with laparoscopic pyeloplasty (LP; 44 cases) or balloon dilatation (BD; 38 cases) from Jan 2010 to Jan 2012, according to patients' preference after consultation. Demographics and clinical parameters were collected. Patients were followed-up at 3, 6, 12, and 24 months. Ultrasonography, intravenous urography, and diuretic renography were applied to evaluate the remission of hydronephrosis. Both groups were comparable with respect to age, UPJO location, gender, and other baseline parameters. Compared to the LP group, patients receiving BD experienced significantly shorter operative time, analgesia time, hospital stay, and urethral catheter indwelling time, and less cost (P<0.001). Three and 6 months after their respective procedures, the success rates of the LP (97.7%, both) and BD (94.7% and 86.8%) groups were similar, and at 12 and 24 months the long-term success rate of LP (95.5%, both) was better than that of BD (78.9% and 71.0%). LP showed better long-term success rate than did BD in the management of UPJO with length of stricture < 2 cm. Considering that BD is more minimally invasive, simpler and easier to perform, and costs less, we recommend it for some selective UPJO patients as the first-line therapy.